PERAN ASURANSI SYARIAH DALAM MEMENUHI KESEHATAN FINANSIAL MASYARAKAT PERKOTAAN - Zuhdi, Muhammad Farhan; Sulaiman Sitompul, Gandi; Fatahilla, Lou; Harahap, Nurhayati (LP2M Universitas Bina Bangsa, 2025)
Sharia insurance plays an important role in facing financial risks faced by urban communities, who are often trapped in a consumptive lifestyle. The background of this research focuses on the challenges faced by society in managing unexpected risks, such as job loss and health costs. The purpose of this study is to explore how sharia insurance can provide financial protection and improve people's financial health. The method used is a qualitative approach with literature analysis and interviews to understand public perception of sharia insurance. The results of the study show that although sharia insurance offers significant benefits, insurance offers benefits while urban communities are exposed to risks in the future. Especially with the lifestyle of people who have a consumptive tendency coupled with professional uncertainty which results in losing their jobs anytime and anywhere, thus allowing people to lose income. Sharia insurance can protect the community from the risk of financial losses of the community, so that the financial health of the community can be fulfilled. The conclusion of this study emphasizes the need for better education about sharia insurance and the development of products that are in accordance with the needs of the community, so that sharia insurance can function optimally in supporting financial stability and the welfare of urban communities.